Selfish giving? - Hayakawa, Tomoko (Traditiones (Ljubljana), 2014)
Following gift exchange theories, this paper explores the concept of giving in volunteering for community care in London. By looking at volunteering motivations, it explores three facets of volunteering: 1) an instrumental use of volunteering as a substitute for paid work, 2) the perceived power inequality between service users and volunteers, 3) the role of voluntary organisations that sets the morality of giving. It concludes that volunteering is characterised by its dual nature, and there is a constant process of negotiation of meaning and appropriation of its expression.
Keywords: cultural anthropology; kulturna antropologija; social work; socialno delo; solidarity; solidarnost; ethics; etika; prostovoljstvo; prostovoljci